FORMULATION AND EVALUATION OF GLIBENCLAMIDE TABLET USING SOLID DISPERSION WITH VARIOUS POLYMERS - Singh, Darshdeep; Dua, J.S; Prasad, D.N. (Asian Journal of Pharmaceutical Research and Development, 2018)
The aim of the present study is to enhance the solubility of water insoluble drug, Glibenclamide by preparing solid dispersion using various polymers and further formulating its tablet. Solid dispersion is an effective way of improving the dissolution rate of poorly water soluble drugs. Hence, Solvent evaporation technique is used for the improvement of the solubility of poorly water-soluble drug Glibenclamide. It is used an adjunct to diet to lower the blood glucose in patients with non-insulin-dependent diabetes mellitus (Type II diabetes). Preformulation studies for Glibenclamide were done such as; determination of Melting point, partition coefficient, solubility studies and λmax. The melting point of procured sample was found to be 173-175ºC. An absorption maximum (λmax) of the drug was observed to be at 245 nm. Drug-polymer compatibility studies were done by preparing physical mixture of drug with PEG 6000 and β-CD. Solid dispersion of Glibenclamide was prepared using drug: polymer (1:1 and 1:3) with sufficient amount of methanol in F1-F6 batches. From the resulted solid dispersion, tablet was compressed using MCC as binder, talc and magnesium stearate as lubricant. Evaluation of the prepared solid dispersion was done by determination of drug content, %yield, FT-IR, stability studies. Characterization of the compressed tablet was done by determining its hardness (2.5-4.1kg/cm3), disintegration time was found 4.02-5.67 minutes, friability 0.25 and results, drug content was found to be 88.87±0.02 which was best observed in F2 batch. %yield was observed to be 96.18±0.34. Batch F2 gives the highest drug release 87.37 ± 0.11.